SCREENING OF SECONDARY METABOLITE COMPOUNDS AND YIELD OF WHITE RHIZOME (Alpinia Galanga L.) EXTRACT THROUGH FOUR EXTRACTION METHODS - Badriyah, Lailatul (LP2M IIK (Lembaga Penelitian dan Pengabdian Masyarakat Institut Ilmu Kesehatan) Bhakti Wiy, 2024)
Background: Health maintenance can be addressed by the utilization of natural medicines derived from plants called traditional medicine. Traditional medicine can be produced from rhizomes, one of include was the white galangal rhizome. The chemical compounds of white galangal rhizome provide numerous benefits in both culinary and health fields. Objective: to obtain the best yield from the four extraction methods used. The extracts obtained were tested qualitatively using chemical reagents. Method: The method employed was a laboratory experiment utilizing various extraction techniques. The results indicate that the yields from maceration, soxhletation, reflux, and infusion were 11.955%, 20.359%, 15.737%, and 9.416%, respectively. The secondary metabolite compounds found in the white galangal rhizome extract were flavonoids, alkaloids, tannins, terpenoids, and saponins. Conclusions: it can be concluded that the extraction method with the best yield results was the soxhletation method.